Fragility curves for hardfill dams under seismic loading / Curvas de fragilidad para presas de hardfill bajo carga sÃsmica - Hurtado-López, Grissel; Mayoral-Villa, Juan Manuel (Tecnología y ciencias del agua, 2020)
Hardfill dams are comprised of cemented granular materials gathered directly from the river bed or its surroundings, or which are by-product of the dam excavation. This fact leads to significant variations in as-built strengths and deformability parameters within the dam body. In this paper, a numerical approach is applied to derive fragility curves for hardfill dams under seismic loading. Fragility curves describe the probability of a structure to experience a certain damage level for a given earthquake intensity measure, providing a relationship between seismic hazard and vulnerability. Both static and seismic responses of the hardfill dam are assessed using tridimensional finite difference analyses carried out with the software FLAC3D, considering increasing levels of seismic intensity. The fragility curves are estimated in terms of peak ground acceleration at the free field, based on the evolution of damage with increasing earthquake intensity. The proposed fragility models allow to characterize the seismic risk of representative hardfill dam typologies and foundation conditions considering the associated uncertainties, and partially fill the gap of data required in performing a risk analysis of this type of dams.